The Relationship between Self Efficacy and Dietary Approaches to Stop Hypertension (DASH) Diet and Blood Pressure of Hypertensive Patients in the Kediri City District - Hariyono; Yuly Peristiowati; Arantrinita (STRADA : Jurnal Ilmiah Kesehatan, 2024)
Hypertension is a prevalent, non-communicable disease with elevated blood pressure. Overconsumption of salt increases blood pressure, posing a risk of stroke and heart attack. The DASH diet aims to lower blood pressure and maintain normal levels. This study aims to explore the relationship between self-efficacy, DAHS diet, and blood pressure in hypertensive patients in the Kediri City sub-district. The study used a quantitative, observational, and cross-sectional approach to analyze the relationship between self-efficacy, the DASH diet, and blood pressure in hypertensive patients. A sample of 100 respondents was surveyed using questionnaires. The results showed that over half (70.0%) had high self-efficacy and adherence to the DAHS diet, while almost half (45.0%) had normal blood pressure. The chi-square test resulted in a p value of 0.000, rejecting the hypothesis.